2017
DOI: 10.2196/humanfactors.6481
|View full text |Cite
|
Sign up to set email alerts
|

Design and Usability of a Heart Failure mHealth System: A Pilot Study

Abstract: BackgroundDespite the advances in mobile health (mHealth) systems, little is known about patients’ and providers’ experiences using a new mHealth system design.ObjectiveThis study aimed to understand challenges and provide design considerations for a personalized mHealth system that could effectively support heart failure (HF) patients after they transition into the home environment.MethodsFollowing exploratory interviews with nurses and preventive care physicians, an mHealth system was developed. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 20 publications
4
91
0
Order By: Relevance
“…Users valued the ability to tailor a system to individual and organisational needs. 94,[97][98][99][100] This functionality could include personalised alerts and reminders, 77,79,93,[100][101][102] the option to set default filters 75,87 and the ability to pin particular information to the screen to appear at all times, enabling comparisons. 77 Benefits were also reported from being able to dynamically add, remove and adjust elements of the system to fit the user's focus and workflow.…”
Section: Flexibility and Individualisationmentioning
confidence: 99%
“…Users valued the ability to tailor a system to individual and organisational needs. 94,[97][98][99][100] This functionality could include personalised alerts and reminders, 77,79,93,[100][101][102] the option to set default filters 75,87 and the ability to pin particular information to the screen to appear at all times, enabling comparisons. 77 Benefits were also reported from being able to dynamically add, remove and adjust elements of the system to fit the user's focus and workflow.…”
Section: Flexibility and Individualisationmentioning
confidence: 99%
“…Based on DSR framework's 3 cycles: they conducted focus groups with end-users in the Relevance cycle; performed a review to identify technology-based interventions for meeting the health prevention needs in the Rigor cycle and they employed usability evaluation methods to iteratively develop and refine mock-ups for a mHealth app in the Design Cycle. Alharbi et al and Alnosayan et al also align their design methodology with the DSR framework's three cycles (Alharbi et al, 2018;Alnosayan et al, 2017).…”
Section: Design-based Mhealth Studiesmentioning
confidence: 99%
“…Additionally, through the use of mobile or web based applications, interaction between physician and patient can be achieved on a consistent basis regardless of distance between both parties (34,35). Studies have shown that mHealth applications can achieve similar utility in urban and rural settings (36), increase patient adherence towards therapy and rehabilitation (37,38), and successfully identify and manage health deteriorations (39). Although preliminary testing demonstrates the potential of mHealth, results are still inadequate due to the limited number of trials that have been performed (28,40).…”
Section: Rural Healthcare Telemedicine and Mobile Health (Mhealth)mentioning
confidence: 99%